Early access to antiretroviral therapy versus standard of care among HIV‐positive participants in Eswatini in the public health sector: the MaxART stepped‐wedge randomized controlled trial. Issue 9 (19th September 2020) - Khan, Shaukat; Spiegelman, Donna; Walsh, Fiona; Mazibuko, Sikhatele; Pasipamire, Munyaradzi; Chai, Boyang; Reis, Ria; Mlambo, Khudzie; Delva, Wim; Khumalo, Gavin; Zwane, Mandisa; Fleming, Yvette; et al.
Abstract: Introduction: The WHO recommends antiretroviral treatment (ART) for all HIV‐positive patients regardless of CD4 count or disease stage, referred to as "Early Access to ART for All" (EAAA). The health systems effects of EAAA implementation are unknown. This trial was implemented in a government‐managed public health system with the aim to examine the "real world" impact of EAAA on care retention and viral suppression. Methods: In this stepped‐wedge randomized controlled trial, 14 public sector health facilities in Eswatini were paired and randomly assigned to stepwise transition from standard of care (SoC) to EAAA. ART‐naïve participants ≥18 years who were not pregnant or breastfeeding were eligible for enrolment. We used Cox proportional hazard models with censoring at clinic transition to estimate the effects of EAAA on retention in care and retention and viral suppression combined. Results: Between September 2014 and August 2017, 3405 participants were enrolled. In SoC and EAAA respectively, 12‐month HIV care retention rates were 80% (95% CI: 77 to 83) and 86% (95% CI: 83 to 88). The 12‐month combined retention and viral suppression endpoint rates were 44% (95% CI: 40 to 48) under SoC compared to 80% (95% CI: 77 to 83) under EAAA. EAAA increased both retention (HR: 1·60, 95% CI: 1·15 to 2·21, p = 0.005) and retention and viral suppression combined (HR: 4.88, 95% CI: 2.96 to 8.05, p < 0.001). We also identified significant gaps in current health systems ability to provide viral load (VL) monitoring with 80% participants in SoC and 66% in EAAA having a missing VL at last contact. Conclusions: The observed improvement in retention in care and on the combined retention and viral suppression provides an important co‐benefit of EAAA to HIV‐positive adults themselves, at least in the short term. Our results from this "real world" health systems trial strongly support EAAA for Eswatini and countries with similar HIV epidemics and health systems. VL monitoring needs to be scaled up for appropriate care management.